2002
DOI: 10.1128/iai.70.7.3904-3914.2002
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus-Zebrafish Model of Bacterial Pathogenesis

Abstract: Due to its small size, rapid generation time, powerful genetic systems, and genomic resources, the zebrafish has emerged as an important model of vertebrate development and human disease. Its well-developed adaptive and innate cellular immune systems make the zebrafish an ideal model for the study of infectious diseases. With a natural and important pathogen of fish, Streptococcus iniae, we have established a streptococcuszebrafish model of bacterial pathogenesis. Following injection into the dorsal muscle, ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
290
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(303 citation statements)
references
References 71 publications
12
290
0
1
Order By: Relevance
“…This was parallel to the results recorded by Chen et al, 2004. The encountered liver lesions could be explained as the liver is the site of replication of many bacterial pathogens (Neely et al, 2002). The serum creatinine and urea levels were significantly increased in all infected groups reflecting the histopathologic lesions found in kidneys of all infected groups.…”
Section: Discussionsupporting
confidence: 74%
“…This was parallel to the results recorded by Chen et al, 2004. The encountered liver lesions could be explained as the liver is the site of replication of many bacterial pathogens (Neely et al, 2002). The serum creatinine and urea levels were significantly increased in all infected groups reflecting the histopathologic lesions found in kidneys of all infected groups.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to having many of the major organs found in humans, zebrafish embryos are transparent, which allows direct visualization of labeled toxin and toxin-induced changes in anatomy and physiology (23). Indeed, these same characteristics have made the zebrafish a widely accepted model for the study of embryonic development and genetics (35) and infectious diseases (36)(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noticeable that the vast majority of individuals displayed no infiltration associated with muscular lesions or degenerating cells, whereas inflammation is often observed at the site of infection either as a means of fighting the infectious agent or repairing the damaged tissue (Miyazaki et al 1999, Neely et al 2002. Some mollusc pathogens were described as inducing large increases in the circulating haemocytes densities (Oubella et al 1993) and others were demonstrated to possess chemoattractants for oyster haemocytes (Cheng & Howland 1979, Howland & Cheng 1982.…”
Section: Discussionmentioning
confidence: 99%